Understanding Web Publications in the Digital Age by Applying Media Intelligence - Milev, Plamen (Research Papers, 2025)
The article explores approaches for analyzing online publications from leading television media in Bulgaria, utilizing modern big data processing methods. By combining quantitative and qualitative analytical techniques, it demonstrates the potential for extracting meaning and identifying trends in the digital media landscape. The study highlights the importance of the concept of media intelligence in analyzing online content and contributes to a better understanding of transformations within the media ecosystem. These approaches also offer practical guidelines for improving the analysis and management of media content.